1999
DOI: 10.1128/aac.43.3.667
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacies of Oral Levofloxacin and Oral Ciprofloxacin in a Rabbit Model of a Staphylococcal Abscess

Abstract: Oral levofloxacin was compared to oral ciprofloxacin in aStaphylococcus aureus subcutaneous abscess model in rabbits. Rabbits were surgically prepared with subcutaneous wiffle balls (43 mm in diameter) and allowed to recover for 4 to 6 weeks. Rabbits were infected by direct injection into the capsule withS. aureus ATCC 29213 (5 × 105 CFU) and were allowed to remain infected for 8 days before the initiation of anti-infective treatment. Efficacy was determined by assessing the bacterial load within the capsule o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Therefore, with respect to these two models, there appears to be concordance between ED 50 /ED 100 doses, fluoroquinolone concentrations and a desirable therapeutic effect. In addition, the serum concentrations and the derived kinetic parameters are consistent with the published literature [40, 47, 58, 59]. The noted limitation of these concentration data is the fact they were obtained in uninfected animals and involved single-dose administration.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, with respect to these two models, there appears to be concordance between ED 50 /ED 100 doses, fluoroquinolone concentrations and a desirable therapeutic effect. In addition, the serum concentrations and the derived kinetic parameters are consistent with the published literature [40, 47, 58, 59]. The noted limitation of these concentration data is the fact they were obtained in uninfected animals and involved single-dose administration.…”
Section: Discussionsupporting
confidence: 84%
“…Deziel et al [37] reported AUC/MIC ratios of approximately 200-300 were needed for effective therapy; however, outcome was highly dependent on the animal model used and frequency of dose administration. Finally, the C max /MIC and AUC/MIC ratios determined from data in the present study may have been even higher in infected animals with diminished hepatic and renal elimination receiving multiple-dose administration [58]. …”
Section: Discussionmentioning
confidence: 99%
“…During this recovery period, the rabbits were observed daily, and the Wiffle ball became walled off and filled with sterile fluid. 13 Approximately 3.0×10 10 cfu S. aureus ATCC 43300 culture was concentrated in 1 mL of 0.9% NaCl and injected into each pre-implanted plastic ball. Two days after infection, 0.5 mL of tissue-cage fluid was withdrawn from each plastic ball for a viable bacteria count.…”
Section: Tissue-cage Infection Modelmentioning
confidence: 99%
“…In addition, MIC- and MPC-related pharmacokinetic/pharmacodynamic (PK/PD) parameters play an important role in the application of the MSW hypothesis to elucidate the development of resistance ( Firsov et al, 2003 ). The tissue-cage model was usually used to study the PK/PD parameters because drug concentrations and the selective amplification of resistant bacteria can be directly measured at the infected site, and the in vivo model also simulates the dynamic relationship among the antimicrobial agents, organism, and pathogens ( Craig, 1993 ; Fernandez et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%